A General Guideline for Vertically Resolved Imaging of Manufacturing Defects in Organic Tandem Solar Cells - Karl, André; Osvet, Andres; Li, Ning; Brabec, Christoph (Advanced Materials Interfaces, 2020)
Organic tandem solar cells recently made great improvements with power conversion efficiencies (PCEs) over 15%, making them attractive for further large-scale production and industrial applications. However, compared to their single-junction counterparts, the complicated device architectures of organic tandem solar cells strongly restrict their processing and upscaling to larger scales. Therefore, fast and reliable quality control measures are crucial for developing organic tandem photovoltaic technologies towards commercialization. Some of the most widely used means for quality control are luminescence imaging and lock-in thermography respectively. While effective techniques, they are limited in some respects. For example, determining the lateral position of a defect is easily possible, while the exact resolution in which layer of a thin film stack a defect is located, is challenging. This is particularly the case for tandem cells with complicated multi-layer cell architectures. This approach to overcome this challenge is the introduction of well-defined artificial defects into certain layers of an organic tandem cell stack and subsequently performing imaging analysis of the defected cells with several complementary methods. The unique response from cells with artificial defects using different imaging techniques and excitation sources can then be transferred to the imaging of devices with naturally occurring manufacturing defects.
CRIS-Team Scopus Importer:2020-05-22
Keywords: defects; imaging; organic tandem solar cells; quality control